DEVELOPING STUDENTS' CREATIVE COMPETENCIES THROUGH PEN DRAWING OF GEOMETRIC BODIES (American Journal of Pedagogical and Educational Research, 2024)
This article fully describes the skills and methods of using modern pedagogical technologies in the process of conducting fine arts classes, applying the renewal processes in pedagogy to educational practice, and providing information about geometric objects to students and young people with the help of pencil drawings.